Sistem Informasi Penjualan dan Stok dilengkapi dengan Mapping Rak pada Toserba: Studi Kasus : Toserba Decky - Mohamad Doris Sambodo Putro; Soetam Rizky Wicaksono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In the digital era, the advancement of information technology is crucial for enhancing operational efficiency in retail businesses. This study aims to design and develop a sales and inventory information system with a shelf mapping feature for Toserba Decky, which faces challenges in managing stock and manual transactions. The methodology employed is the Waterfall approach, encompassing requirements analysis, design, implementation, and system testing. Data was collected through direct observation, literature review, and analysis of the store's shelf layout. The findings indicate that the developed system can improve data accuracy, reduce recording errors, and expedite product searching. The implications of this research suggest that an effective information system in managing transactions and inventory can enhance operational efficiency and customer satisfaction. This study recommends regular system updates and technical support to ensure optimal system performance and security.